A településfejlesztési koncepció és a faluosztályok elmélete. Emberképünk tizenöt évvel ezelőtt - Juhász, Pál (Tér és Társadalom, 1988)
In the second half of the 1960s the economic policy in Hungary was changed, parallel to the reform of the system of economic management. The proportion of investments in infrastructure was increasing, a program for the industrialization of the countryside was launched, the financial system of local councils was modified, endeavours were made to counterbalance the inequalities of spatial development etc. The National Settlement Development Concept divided the territory of Hungary into various districts of provision. Three hierarchical levels were distinguished for the basic-, the medium- and the high level institutions. Centres of these districts were indicated and settlements were classified accordingly. This served as a rationale for the state policy of redistribution. During the 1970s, the capital funds for infrastructure development and state housing constructions were allocated, the units of spatial administration, the school districts and health care districts were designated in the spirit of the above hierarchy. This was parallelied by a centralization wave: schools, co-operatíves and enterprises got amalgamated. Iván SZELÉNYI’s critique of this development policy was formulated in the theory of settlement classes. It says that a consistently biased redistribution of centralized income leads to a re-evaluation of the citizens’ properties (the value of landed properties in leading hierarchical centres increases while properties become devaluated in settlements which are not being developed) and local inequalities in the labour market increase. Therefore the generated migration processes speed up social segregation. Families with financial or cultural capital move to centres while the poor have no choice but to stay in settlements which loose their institutions and intellectuals, or, in lack of dwelling, they are constrained to move to such settlements. Experience of the past 15 years has given justice to SZELÉNYI’s hypotheses but has also indicated migrations with different motives. Both SZELÉNYI and the Settlement Development Concept expected people to strive after promotions within the state- and co-operative hierarchy but following the mid1970s new family strategies have been developed with the second economy becoming organized into a coherent system.